Magnesium from bioresorbable implants: Distribution and impact on the nano- and mineral structure of bone. (January 2016) - Grünewald, T.A.; Rennhofer, H.; Hesse, B.; Burghammer, M.; Stanzl-Tschegg, S.E.; Cotte, M.; Löffler, J.F.; Weinberg, A.M.; Lichtenegger, H.C.
Abstract: Biocompatibility is a key issue in the development of new implant materials. In this context, a novel class of biodegrading Mg implants exhibits promising properties with regard to inflammatory response and mechanical properties. The interaction between Mg degradation products and the nanoscale structure and mineralization of bone, however, is not yet sufficiently understood. Investigations by synchrotron microbeam x-ray fluorescence (μXRF), small angle x-ray scattering (μSAXS) and x-ray diffraction (μXRD) have shown the impact of degradation speed on the sites of Mg accumulation in the bone, which are around blood vessels, lacunae and the bone marrow. Only at the highest degradation rates was Mg found at the implant–bone interface. The Mg inclusion into the bone matrix appeared to be non-permanent as the Mg-level decreased after completed implant degradation. μSAXS and μXRD showed that Mg influences the hydroxyl apatite (HAP) crystallite structure, because markedly shorter and thinner HAP crystallites were found in zones of high Mg concentration. These zones also exhibited a contraction of the HAP lattice and lower crystalline order.